Immediate breast reconstruction using permanent expanders - Gustavo Felipe Pasqual; Luciana De Vasconcelos Sá Pasqual (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: Breast cancer has become increasingly prevalent, resulting in a greater number of patients undergoing mastectomies. Post-mastectomy immediate reconstruction is an important alternative treatment in the various stages of breast reconstruction. METHODS: A retrospective study was conducted with 34 patients who underwent mastectomy or adenomastectomy, with or without preservation of the areola-papillary complex, followed by immediate reconstruction using a permanent expander. The expander used was of the Becker type 35 and anatomically shaped, having a volume ranging from 365 to 565 ml, with the 460-ml expander being the most frequently used. RESULTS: The results were considered "highly satisfactory" by 85% of the patients. The complication rate was 17.6%; two patients had skin necrosis on the edges of the surgical wound, two patients presented scar retraction in the surgical wound, one patient presented seroma, and only one patient had expander loss because of late infection after the start of chemotherapy. Thirteen patients underwent radiotherapy, of whom 53% (n = 7) had mild radiodermatitis and 30% (n = 4) had moderate radiodermatitis without other complications. CONCLUSION: Immediate reconstruction using definitive expanders presents a good treatment option for patients who will undergo total or partial mastectomy.